Productivity Improvement Based Systematic Layout Planning and 5S (Case Study: CV. Mutya, Indonesia) - Calvin Aidil Febri; Anita Susilawati (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2022)
The amount of productivity had not met the target demand of customers in CV. Mutya. This happens could be due to un-optimal the facility lay out such as the distance of material working flow and un-effective the work processes. This paper aim is to improve productivity of wooden pallets product in CV. Mutya, Indonesia. The Systematic Layout Planning (SLP) method was used to improve the facility layout at CV. Mutya. To improve the work process was used 5S methods. The material transfer flow distance in the initial layout of CV. Mutya was 48.2 meters. Then, designing a new layout resulted the material displacement flow distance of 41.5 meters. Based the SLP method, to find out the root of the problem that occurs was employed the cause and effect analysis and work improvement using 5S. The 5S method was used to improve the conditions of the work environment and change attitudes by applying arrangement, cleanliness and discipline in the workplace.